Investigation of Perception of Quality of Life and Psychological Burden of Patients Undergoing Hemodialysis-Quality of Life of Hemodialysis Patients - Nikos Rikos; Anna Kassotaki; Chara Frantzeskaki; Maria Fragiadaki; Andreas Mpalaskas; Georgios Vasilopoulos; Manolis Linardakis (MDPI AG, 2023)
Chronic kidney disease (CKD) has a significant impact on the life of patients undergoing chronic periodic hemodialysis. It negatively affects their social, economic and family status, and particularly their psychological well-being. The aim of this study was to investigate the perception of the quality of life (QoL) and psychological burden of patients undergoing hemodialysis. A cross-sectional study was conducted with 63 patients. Τhe majority were men (63.5%), and the mean age of the patients was 66.7 years (±12.9) with 61.9% aged 65-89 years. Data collection was performed in 2021 using the Hospital Anxiety and Depression Scale (HADS) and the Kidney Disease and Quality of Life-Short Form (KDQOL-SF™) research tools, and their relationships were assessed using parametric and non-parametric methods. Moderate to mild levels of Anxiety and Depression were found. Physical and Mental Composite Scores were mild to moderate, with the Mental Composite Score being significantly higher (p < 0.05). Anxiety and Depression were significantly correlated with lower QoL (p < 0.05), while a higher educational level was correlated with lower Depression Symptom Levels and higher QoL for Disease Symptoms, Disease Effects, Physical Functioning, Vitality and Overall Health (p < 0.05). A higher number of years of hemodialysis was correlated with lower levels of Anxiety and higher levels of Quality of Sleep (p < 0.05). Ease of Access to the Hemodialysis Unit was correlated with lower levels of Social Support (p < 0.05). The highest Mental Composite Scores were also correlated with a higher level of education, with patients living in urban areas, and with a higher monthly income (p < 0.05). Patients with moderate or severe levels of Anxiety and Depression had a lower QoL in the Physical and Mental Composite Scores, indicating their dependence on the appropriate medical, nursing and social environment in order to attain higher levels of well-being, leading to the improvement of patients' health. This study was not registered.